Understanding intermediate algebra - Moon, Robert G.; Klentos, Gus. (Columbus, Ohio : Merrill Pub. Co., 1987)
A textbook to develop understanding and computational skills with the techniques usually found in a second-level algebra course.
Includes index.
Keywords: Algebra; Algebra